DIGITAL TRANSFORMATION OF THE RUSSIAN LEGAL PROFESSION - Volodina, Svetlana; Gavrilov, Sergey (Revista Inclusiones, 2020)
The article describes the information (digital) ecosystem of the Russian legal profession. It determines theoretical and methodological foundations for establishing an ecosystem and key approaches to its formation. The study aims at substantiating the need to create a national system of professional legal assistance (services) and identifying the main factors that determine the quality of the integrated information system of the Russian legal profession as the core of its ecosystem. To ensure the correlation of corporate management with corporate IT systems under development, the authors of the article use the cybernetic approach. Natural ecosystems are cybernetic and digital ecosystems are based on natural ecosystems. They both have similar aspects related to competition and cooperation between various actors. The study has concluded that the integrated information system of the Russian legal profession can be formed in conformity with the project approach at the initial stages of deploying certain subsystems (analysis, project conception, implementation and adoption). For example, the first functional module (the all-Russian information system for the automated distribution of orders for the provision of legal assistance as intended) is under development on a project basis. However, any system should be constantly developed (improved) on a functional basis.